2015
DOI: 10.1111/ced.12626
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy in the elderly

Abstract: In this small survey, the first of its kind to focus on elderly patients, phototherapy appears to be well-tolerated, safe and efficacious in the short term. Further thought and investigation should be given to delivering phototherapy to an ageing population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
28
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 15 publications
6
28
2
5
Order By: Relevance
“…Our data illustrate that antihistamine consumption is reduced following administration of NB-UVB, even in patients with psoriasis, 11 confirming the widespread observation that NB-UVB is effective to control pruritus. 24,25 Other common conditions, notably eczema 26,27 and urticaria, 28 also show good response to this treatment, thereby adding to indirect net savings by creating synergy on staff and equipment cost.…”
Section: Discussionmentioning
confidence: 99%
“…Our data illustrate that antihistamine consumption is reduced following administration of NB-UVB, even in patients with psoriasis, 11 confirming the widespread observation that NB-UVB is effective to control pruritus. 24,25 Other common conditions, notably eczema 26,27 and urticaria, 28 also show good response to this treatment, thereby adding to indirect net savings by creating synergy on staff and equipment cost.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, these patients lack specific skin lesions, and no obvious cause for their chronic (often generalized) pruritus (ie chronic idiopathic pruritus) can be found. Phototherapy can effectively reduce itching in these elderly patients (by up to 80%) and has a minimal risk of acute side effects if the proper UV doses are applied and patients are closely monitored during UV treatment courses . Long‐term side effects, such as the acceleration of skin ageing or higher skin cancer risk, especially in patients with a history of excessive, lifetime sun exposure or who have already received the highest advised cumulative number of UV treatments (around 150‐200 treatments of PUVA or 300 for NB‐UVB), however, have to be considered.…”
Section: Uv Therapy In Other Diseases With Chronic Pruritusmentioning
confidence: 99%
“…Thus, UV therapy is a beneficial and relatively safe antipruritic treatment option in elderly patients who do not have pre‐existing severe UV‐induced skin damage or other skin cancer risk factors. However, all patients who receive long‐term UV treatments, irrespective of their ages, should undergo regular skin cancer surveillance …”
Section: Uv Therapy In Other Diseases With Chronic Pruritusmentioning
confidence: 99%
“…5 Presence of comorbidities and polypharmacy that commonly accompany geriatric patients also require clinicians to give a lot more consideration when deciding therapy compared to the adults. To our knowledge, there are only 2 studies that evaluated phototherapy specifically in geriatric population, which are a study in Turkey by Bulur et al 6 and in the United Kingdom by Powell et al 7 Bulur et al found that mycosis fungoides was the most common indication for phototherapy in geriatric patients, presenting in 29.5% of 95 included patients, and followed by psoriasis, pruritus, and lichen planus. 6 Powell et al reported 51% of 37 included patients were diagnosed with psoriasis, followed by eczema, nodular prurigo, and pruritus.…”
Section: Discussionmentioning
confidence: 99%